Pengaruh Prinsip Syariah Pada Kinerja Keuangan Bank Syariah Di Indonesia - Ramadhani, Nur Ainie; Susetyo, Achmad Budi (Jurnal Ekonomi dan Bisnis, 2025)
Financial performance of Islamic banks in Indonesia. Islamic banks rely on Islamic principles such as prohibition of usury, fairness in transactions, and fair risk sharing. This study uses literature study and quantitative descriptive analysis. In addition, a literature study approach from accredited journals is also used. Return on Assets (ROA), Return on Equity (ROE), and Financing to Deposit Ratio (FDR) are some of the financial performance indicators used. The results of the study indicate that regular application of Islamic principles improves financial performance, increases customer trust, and improves the stability of Islamic banks. Thus, Islamic principles create ethical values ​​in banking and improve financial performance.   Hasil keuangan bank syariah Indonesia. Prinsip-prinsip syariah seperti larangan riba, keadilan dalam transaksi, dan pembagian risiko yang adil adalah dasar bagi bank syariah. Studi pustaka dan analisis deskriptif digunakan dalam penelitian ini. Selain itu, metodologi studi literatur dari jurnal terakreditasi juga digunakan. Beberapa indikator kinerja keuangan yang digunakan termasuk Return on Assets (ROA), Return on Equity (ROE), dan Financing to Deposit Ratio (FDR). Studi menunjukkan bahwa penerapan prinsip syariah secara teratur meningkatkan kinerja keuangan, meningkatkan kepercayaan nasabah, dan meningkatkan stabilitas bank syariah. Oleh karena itu, nilai-nilai etis dan kinerja finansial diperkuat oleh prinsip syariah.